FIELD SCREENING FOR POWDERY MILDEW DISEASE RESISTANCE IN SUNFLOWER (Helianthus annuus L.) GENOTYPES - Y. PRUDHVI KUMAR REDDY; B. V. RAVI PRAKASH REDDY; K. VENKATARAMANAMMA; P. SHANTHI (The Journal of Research ANGRAU, 2024)
NA